Numerical Simulation of Subsurface Penetrating Radar in Isidis Planitia on Mars for China's First Mission to Mars. Issue 1 (February 2021) - Wang, Ying; Feng, Xuan; Liang, Wenjing; Zhou, Haoqiu; Dong, Zejun; Li, Xiaotian; Xue, Cewen
Abstract: The water ice exploration mission is an important scientific target of China's first Mission to Mars. The high frequency full polarimetric subsurface penetrating radar (SPR) system onboard the landing rover can carry out high-resolution imaging of the near-surface area of Mars, which is an important tool for detecting the presence of shallow water ice and soil structure. At present, most of the radar detection simulations are based on low-frequency antennas to analyze the geological structure of Mars down to several kilometers, with low resolution, which is difficult to detect the subsurface structure in the near-surface accurately. Considering topographic relief, interface roughness, subsurface rock, water ice, and permittivity changes at different layers, a three-dimensional near-surface model in the Isidis Planitia on Mars is established. The interpretation of the forward simulation results is of reference value for future Mars exploration missions.